2019
DOI: 10.1002/stem.2928
|View full text |Cite
|
Sign up to set email alerts
|

Xist Intron 1 Repression by Transcriptional-Activator-Like Effectors Designer Transcriptional Factor Improves Somatic Cell Reprogramming in Mice

Abstract: Xist is the master regulator of X chromosome inactivation. In order to further understand the Xist locus in the reprogramming of somatic cells to induced pluripotent stem cells (iPSCs) and in somatic cell nuclear transfer (SCNT), we tested transcription-activator-like effectors-based designer transcriptional factors (dTFs), which were specific to numerous regions at the Xist locus. We report that the selected dTF repressor 6 (R6) binding the intron 1 of Xist, which caused higher H3K9me3 followed by X chromosom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Increasing evidence has indicated that regulating epigenetic modifications could increase somatic cell reprogramming efficiency (Zhang J. et al, 2019). Recent studies suggested that RNA m 6 A modifications can act as a functional regulator in cell reprogramming (Bao et al, 2015; Figure 3).…”
Section: Role Of M 6 a In Cell Reprogrammingmentioning
confidence: 99%
“…Increasing evidence has indicated that regulating epigenetic modifications could increase somatic cell reprogramming efficiency (Zhang J. et al, 2019). Recent studies suggested that RNA m 6 A modifications can act as a functional regulator in cell reprogramming (Bao et al, 2015; Figure 3).…”
Section: Role Of M 6 a In Cell Reprogrammingmentioning
confidence: 99%
“…However, the RNAi-based method is disadvantageous because it can only enhance the developmental competence of male but not female mouse SCNT embryos [28], whereas the knockout of maternal Xist allele can improve the developmental efficiency of both male and female mouse SCNT embryos [11]. Interestingly, a recent study reported that a new method via the epigenetic modification of the Xist gene can increase the developmental ability of mouse embryos [31].…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that lncRNA Xist may play a role in a new approach for improving the quality of porcine parthenogenetic embryos. lncRNA Xist ( Zhang et al, 2019b ) facilitates cells development in somatic cells by TALE-based designer transcriptional factor, and regulates embryonic stem cells’ fates ( Chelmicki et al, 2014 ; An et al, 2020 ). lncRNA Xist promotes hair follicle regeneration in Dermal papilla cells via regulating miR-424/Shh axis to activate hedgehog signaling ( Lin B.J.…”
Section: The Role Of Lncrna Xist In Non-cancer Diseasesmentioning
confidence: 99%